Integrating ecosystem service value into the evaluation of sustainable land use in fast-growing cities: A case study of Qingdao, China - Xiaokang Li; Lin Lei; Jintao Li (Ecological Indicators, 2023)
Integrating ecosystem service value (ESV) into the evaluation system for sustainable land use (SLU) in fast-growing cities is an effective way to implement Sustainable Development Goals (SDGs) 15 and 11 of the United Nations' 2030 Agenda for Sustainable Development. Taking ESV as the intermediate parameter, six sustainability indicators were developed to evaluate SLU from two dimensions: sustainable land ecosystem services and economic development. These indicators are the total supply and demand index (RT) of ecosystem services, the potential supply and demand index (RP) of ecosystem services, the ecological cost index per unit of GDP (RC), the eco-economic coordination index (RD), the eco-economic equilibrium index (RE), and the ESV-based sustainable land use index (RS). Empirical research was conducted in Qingdao, a fast-growing city in eastern China, to verify the validity of the indicators. Five sets of Landsat TM/ETM/OLI remote sensing images from 1996, 2005, 2010, 2015, and 2017 were used to analyze the land use and ESV changes in Qingdao. The results indicate that land use changes in fast-growing cities significantly affect the ESV. The decrease in the area of ecological land and the expansion of construction land caused by rapid urbanization reduced ESV. The RC and RD of Qingdao were sustainable, while the RT and RP were unsustainable, and the RE showed volatility, which reduced the evaluation level of SLU in Qingdao from extremely strongly sustainable (L1) to moderately sustainable (L3). Thus, it is necessary to improve the ESV of Qingdao. Optimization strategies for promoting SLU in Qingdao are proposed based on the results, confirming that the evaluation provides guidance for land use management.